Cryptococcus Neoformans Infection in Non-HIV Cryptococcal Meningoencephalitis - Mutiara, Frederica; Novianingtyas, Dwi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Cryptococcus meningoencephalitis is an inflammation of the meningeal membrane due to Cryptococcus fungal infection. This fungus attacks the Central Nervous System (CNS) with a low immune system, especially in patients infected with advanced Human Immunodeficiency Virus (HIV), opportunistic diseases related to Acquired Immunodeficiency Syndrome (AIDS), and non-HIV patients with long-term corticosteroid treatment, organ transplants, lymphoreticular malignancies. This article reports the case of a 49-year-old female patient with complaints of decreased consciousness accompanied by severe headaches experienced during the previous 14 days. There was impaired nerve function also. The patient was found to have reduced Glasgow Coma Scale (GCS), neurologic deficit, and rigidity. Laboratory examinations found leukocytosis, with a positive brain fluid analysis examination of budding fungal cells in Indian ink staining and growing Cryptococcus neoformans species in SDA culture and non-reactive HIV blood test results. Cryptococcus meningoencephalitis can occur in patients with non-HIV infection. The use of NSAIDs can impair the immune system. A definitive diagnosis is established by finding the fungus.